2003
DOI: 10.1034/j.1600-0609.2003.00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression levels of hsc70 and hsp60 are developmentally regulated during B‐cell maturation and not associated to childhood c‐ALL at presentation or relapse

Abstract: Heat shock proteins are potent regulators of apoptosis, and so they may also be involved in normal cellular differentiation and cancerogenesis. We used quantitative two-dimensional gel electrophoresis for determining whether either the constitutive chaperonic heat shock cognate protein 70 (hsc70) or heat shock protein 60 (hsp60) contribute to B-cell differentiation and leukemogenesis. We compared the expression of these hsps in normal peripheral blood (PB) CD19+ B-cells, in pediatric bone marrow (BM) CD19+ CD1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…Our study revealed significantly higher Hsp60 gene expression in the peripheral blood of patients, at the time of leukemia diagnosis, compared with healthy controls. Our gene expression data agrees with the observations of Wehner et al [37] who demonstrated that Hsp60 protein expression did not differ between bone marrow samples of pediatric patients during onset or relapse of c-ALL and healthy controls. Contrary to the findings of Wehner et al [37], Emura et al [38] found a positive association between the level of intrinsic expression of Hsp60 and an unfavorable prognosis for newly diagnosed patients with AML.…”
Section: Discussionsupporting
confidence: 95%
“…Our study revealed significantly higher Hsp60 gene expression in the peripheral blood of patients, at the time of leukemia diagnosis, compared with healthy controls. Our gene expression data agrees with the observations of Wehner et al [37] who demonstrated that Hsp60 protein expression did not differ between bone marrow samples of pediatric patients during onset or relapse of c-ALL and healthy controls. Contrary to the findings of Wehner et al [37], Emura et al [38] found a positive association between the level of intrinsic expression of Hsp60 and an unfavorable prognosis for newly diagnosed patients with AML.…”
Section: Discussionsupporting
confidence: 95%
“…Studies conducted in lymphocytes isolated from human peripheral blood mononuclear cells reported that Hsc70 expression regulates the development of B lymphocytes and is a potential target of tyrosine kinase activity in T lymphocytes. It has been associated with increases in inflammation and susceptibility to autoimmunity as well as regulating the myocardial immune response [37][38][39][40].…”
Section: Co-chaperoningmentioning
confidence: 99%
“…42) Flot2 protein is assembled in a complex that contains activated glycosylphosphatidylinositol-linked cell adhesion molecules. Over expression of flot2 resulted in induction of filopodia.…”
Section: Immunohistochemical Analysis Of Ezrin In Rat Placentamentioning
confidence: 99%